A new surgical technique for left atrial reduction in giant left atrium - Ríos-Ortega, Josías C. (2023)
Objective: The study objective was to evaluate the safety and clinical and echocardiographic outcomes of a new surgical technique in adult patients diagnosed with a giant left atrium. Methods: We analyzed a cohort of patients who underwent left atrium reduction surgery between January 2016 and June 2020 performed by a specialized surgical team in 2 national reference centers in Lima, Peru. We assessed the major adverse valvular-related events and the New York Heart Association functional class as primary clinical outcomes. Also, our primary echocardiographic endings were the diameter, area, and volume of the left atrium. We assessed these variables at 3 time periods: baseline (t0), perioperative period (t1), and extended follow-up (t2: 12 3.4 months). We carried out descriptive and bivariate exploratory statistical analysis for dependent measures. Results: We included 17 patients, 70.6% of whom were women. Rheumatic mitral valve disease (76.5%) was the main etiology. We performed 14 (82.4%) mitral valve replacements and 3 repairs. Major adverse valvular-related events occurred in 1 patient (5.9%) (hemorrhagic stroke) at t1. A significant reduction in the size of the left atrium was observed: diameter (77 mm vs 48 mm, P<.001), area (75 cm2 vs 31 cm2P<.001), and volume (332 cm3 vs 90 cm3 , P<.001). Compared with t0 and t1, these echocardiographic findings remained without significant changes during t2. Conclusions: Our surgical left atrium reduction technique was associated with improved clinical functionality and reduced left atrium measures in patients with a giant left atrium undergoing mitral valve surgery. (JTCVS Techniques 2023;17:56-64)